2010
DOI: 10.1002/elps.200900325
|View full text |Cite
|
Sign up to set email alerts
|

Pyrosequencing‐based strategy for a successful SNP detection in two hypervariable regions: HV‐I/HV‐II of the human mitochondrial displacement loop

Abstract: Forensic analysis of mitochondrial displacement loop (D-loop) sequences using Sanger sequencing or SNP detection by minisequencing is well established. Pyrosequencing has become an important alternative because it enables high-throughput analysis and the quantification of individual mitochondrial DNAs (mtDNAs) in samples originating from more than one individual. DNA typing of the mitochondrial D-loop region is usually the method of choice if STR analysis fails because of trace amounts of DNA and/or extensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…A histogram for homoplasmic 3460G > A detection of pyrosequencing assay was shown as a reference (D). entire mitochondrial genome was only possible using various individual pyrosequencing reactions on a number of PCR fragments [22]. In this study, we carried out 4 individual PCR amplifications and 4 pyrosequencing reactions (40µl of PCR solution) for each sample to achieve the 4 mutation analyses (11778G > A, 14484T > C, 3460G > A and 13708G > A).…”
Section: Comparison Of Three Snp Typing Methodologies In Detecting Lhmentioning
confidence: 99%
“…A histogram for homoplasmic 3460G > A detection of pyrosequencing assay was shown as a reference (D). entire mitochondrial genome was only possible using various individual pyrosequencing reactions on a number of PCR fragments [22]. In this study, we carried out 4 individual PCR amplifications and 4 pyrosequencing reactions (40µl of PCR solution) for each sample to achieve the 4 mutation analyses (11778G > A, 14484T > C, 3460G > A and 13708G > A).…”
Section: Comparison Of Three Snp Typing Methodologies In Detecting Lhmentioning
confidence: 99%
“…MDA-based WGA has been frequently used in DNA sample preparation for genotyping and sequencing in recent years [18-21]. High call rates (97.5%) and excellent concordance rates were achieved from WGA samples using high-density SNP arrays [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In these circumstances DNA typing of mitochondrial displacement loop (D-loop) region is usually the method of choice for investigators since most of the variations in mtDNA among individuals are found within the D-loop and can be useful for discriminating among unrelated individuals. 80 The HV I/HV II mtDNA linear array assay, decreases sequencing efforts substantially and thereby reducing the cost and time in forensic analysis. 81 …”
Section: Methods Of Mtdna Analysismentioning
confidence: 99%